Особливості макро- і мікроскопічної структури лімфатичних вузлів свиней різних вікових груп в постнатальний період онтогенезу - Гаврилін, Павло Миколайович; Gavrilin, P.; Gavrilin, P. N.; Gavrylin, P.; Gavrylin, P. M.; Havrylin, P. M.; Havrylin, P.; Gavrilin, Pavlo; Gavrilin, Pavel; Тішкіна, Наталія Миколаївна; Tishkina, Natalіia; Tishkina, Natalya; et al. (Харківська державна зооветеринарна академія, 2017)
Досліджували соматичні і вісцеральні лімфатичні вузли свиней білої української породи 2-х та 6-ти місячного віку з використанням комплексу класичних гістологічних методик. Встановили, що лімфатичні вузли свиней на органному рівні мають вигляд конгломератів, утворених зрощенням між собою окремих одиниць (часток) вузлів, об’єднаних єдиною сполучнотканинною стромою, яка формує два типи воріт «справжні» та «несправжні», які розміщені на протилежних полюсах конгломерату вузлів. Паренхіма лімфатичних вузлів має часточкову структуру, де кожна часточка складається з різних у функціональному відношенні клітинних зон та лімфатичних синусів. Найбільш високоспеціалізованими зонами є одиниці глибокої кори і лімфатичні вузлики, які займають більшу частину площі лімфоїдної паренхіми вузла. З віком спостерігається перерозподіл площі між вузликами і одиницями глибокої кори, за рахунок активного формування вузликів з реактивними центрами розмноження. Низько-спеціалізованими зонами в паренхімі є мозкові тяжі, площа яких не значна та істотно не змінюється з віком. Исследовали соматические и висцеральные лимфатические узлы свиней белой украинской породы 2-х и 6-ти месячного возраста с использованием комплекса классических гистологических методик. Установили, что лимфатические узлы свиней на органном уровне имеют вид конгломератов, образованных сращением между собой отдельных единиц (долек) узлов, объединенных общей соединительнотканной стромой, которая формирует два типа ворот «настоящие» и «ненастоящие», расположенных на противоположных полюсах конгломерата узлов. Паренхима лимфатических узлов имеет дольчатую структуру, где каждая долька (сегмент) состоит из разных в функциональном отношении клеточных зон и лимфатических синусов. Наиболее высокоспециализированными зонами являются единицы глубокой коры и лимфатические узелки, которые занимают большую часть площади лимфоидной паренхимы узла. С возрастом наблюдается перераспределение площади между узелками и единицами глубокой коры, за счет активного формирования узелков с реактивными центрами размножения. Низко-специализированными зонами в паренхиме являются мозговые тяжи, площадь которых не значительна и существенно не меняется с возрастом. We investigated somatic and visceral pigs lymph nodes Ukrainian white breed 2 and 6 months of age using complex classical histological methods. Established, that lymph nodes of pigs on organ level have the conglomerates look formed by crossing together individual units (shares) nodes combined total stroma connective tissue, that forms two types of gates "real" and "unreal" are placed at opposite poles conglomerate units. "Unreal" gate is located on the external surface of separate parts of lymphodes as deepening, through that in the layer of parenchyma Lymph nodes penetrate brining (episodic) lymphatic vessels in composition mighty capsules trabecula, that walk away from a capsule. On the opposite side of conglomerate lymph bulge of the "real" gate, form blood (by an artery and vein) and lymphatic bearing- out (efferent) vessels, is unclearly expressed. Every lymph node of pig of domestic consists of connective stroma (capsules and trabecul (capsular, collar, intermediate crust and cerebral)), parenchyma and system of lymphatic sinus. At the microscopic searching of lymph nodes set the characteristic exceed respectively parenchyma components above , stromal where relative area of parenchyma for two-month piglets presented 85-89 % and for six-month pigs –80-83 %. Here relative area of connective tissue stroma of lymph nodes did not exceed according to 15 % and 19 %overall areas of cut of lymph nodes. The parenchyma of lymph nodes is presented by lympha tissue basis of that is made by a reticulum tissue together with the cages of lymphocytic row and system of sinus. Parenchyma of lymph nodes has lobed structure, where each slice consists of functionally different cell areas and lymph sinuses. The most highest specialized areas are units of deep crust and nodules lymph, which cover most of the space lymphoid parenchyma site. There is a redistribution of space between knots and units of deep crust, formation by active nodes with reactive centers of reproduction. With age low specialized areas in parenchyma are brain band, whose area is small and does not change with age. With age in lymph nodes of 6-montly pigs of relative area of cerebral cords diminishes almost in two times and does not exceed 12.43-14.91 % overall of relative area.
Особенности макро- и микроскопической структуры лимфатических узлов свиней разных возрастных групп в постнатальный период онтогенеза
Features macro and microscopic structure pigs lymphatic nodes in different age groups postnatal period of ontogenesis
Keywords: свиня свійська; domestic pig; лімфатичні вузли; lymph nodes; конгломерат; conglomerate; сегменти; segments; функціональні зони; functional ares; лімфоїдна паренхіма; lymphoid parenchyma